2010
DOI: 10.1097/01.naj.0000366056.06605.d2
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Practice: Step by Step: The Seven Steps of Evidence-Based Practice

Abstract: This is the second article in a new series from the Arizona State University College of Nursing and Health Innovation's Center for the Advancement of Evidence-Based Practice. Evidence-based practice (EBP) is a problem-solving approach to the delivery of health care that integrates the best evidence from studies and patient care data with clinician expertise and patient preferences and values. When delivered in a context of caring and in a supportive organizational culture, the highest quality of care and best … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
322
0
49

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 429 publications
(434 citation statements)
references
References 5 publications
(3 reference statements)
2
322
0
49
Order By: Relevance
“…The greatest barriers were lack of time and lack of skills to find and manage research evidence [12]. Other barriers such as Language barriers, inability to access, interpret, and use the research findings, and knowledge deficit about EBP were reported [13,14]. Studies in Arabic countries showed approximate results.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…The greatest barriers were lack of time and lack of skills to find and manage research evidence [12]. Other barriers such as Language barriers, inability to access, interpret, and use the research findings, and knowledge deficit about EBP were reported [13,14]. Studies in Arabic countries showed approximate results.…”
Section: Introductionmentioning
confidence: 80%
“…Knowledge, skills, attitudes and practice are the keystone of implementing EBP [10,17]. Findings from previous studies indicated that nurses' knowledge, attitudes and beliefs about EBP can play a crucial role to the extent to which EBP is implemented [13,14,18]. Consequently, Knowledge, attitudes can potentially predict future behavior in regard to EBP implementation [1,9].…”
Section: Introductionmentioning
confidence: 99%
“…Cabe recordar que, en este trabajo, se denominan 'prácticas de referencia' a las buenas prácticas identificadas mediante una revisión sistemática de la literatura científica, que al ser implementadas dentro de las organizaciones han llevado a estas a resultados exitosos [28].…”
Section: Revisión De La Literaturaunclassified
“…After implementing the evidence-based guideline, it is important to monitor and evaluate any changes in outcomes so that positive effects can be supported and negative ones can be remedied [28]. Monitoring the effect of evidence-based practice change on health care quality and outcomes can help identify flaws in implementation and determine which patients are most likely to benefit.…”
Section: Evaluation Planmentioning
confidence: 99%